Pharmaceutical Design and Structure-activity Relationships of Psoralen and Derivatives - Hu, Ying-Yue; Wang, Yun-Can; Qin, Wen-Xiu; Yu, Shuo; Dai, Si-Yang; Pei, Yue-Hu; Li, Chang; Yang, Yi-Hui (Current Pharmaceutical Design, 2025)
Psoralen, the simplest linear furanocoumarin, is derived from many medicinal plants, such as Psoralea corylifolia L., Glehnia littoralis Fr. Schmidt ex Miq., and Peucedanum decursivum (Miq.) Maxim. It has been used for treating osteoporosis and some skin disorders, including vitiligo, psoriasis, and atopic eczema. This review focuses on the pharmaceutical design of psoralen and the structure-activity relationships (SARs) of its derivatives. It also includes the biosynthetic pathways, metabolic characteristics, metabolites, and clinical uses of psoralen, as well as its toxicity/side effects and relevant mechanisms. Psoralen, as a promising drug lead compound, is structurally modified to develop numerous derivatives with remarkable biological activities. SARs discussed herein can guide the design and development of novel psoralen-based derivatives for use in pharmaceuticals and widen their therapeutic potencies.
Keywords: biosynthetic pathway